Stereotip dan Prasangka dalam Komunikasi Lintas Budaya : Studi Kasus Mahasiswa Suku Jawa Terhadap Etnis Madura di Universitas Trunojoyo Madura - Nelly Fitri Dwiyanti (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study explores the stereotypes and prejudices held by Javanese students toward the Madurese ethnic group at the University of Trunojoyo Madura. Communication, as a fundamental social need, plays a crucial role in building relationships and understanding emotions. In the context of intercultural communication, differences in social and cultural backgrounds can trigger stereotypes that negatively affect interactions. To understand the perspectives of Javanese students in forming stereotypes about the Madurese, this research applies Standpoint Theory, which emphasizes that a person’s viewpoint is shaped by their social position and life experiences. This study employs a qualitative approach with a phenomenological paradigm, collecting data through in-depth interviews and observation. The findings reveal that Javanese students tend to perceive Madurese people as speaking harshly, although some acknowledge that such perceptions do not represent the entire ethnic group. Efforts to overcome stereotypes are made through increased interaction. This study highlights the importance of intercultural understanding in reducing misunderstandings and fostering